Comparative diet-gut microbiome analysis in Crohn’s disease and Hidradenitis suppurativa - Cronin, Peter; McCarthy, Siobhan; Hurley, Cian; Ghosh, Tarini Shankar; Cooney, Jakki C.; Tobin, Ann-Marie; Murphy, Michelle; O’Connor, Eibhlís M.; Shanahan, Fergus; O’Toole, Paul W. (Frontiers in Microbiology, 2023)
The chronic inflammatory skin disease Hidradenitis suppurativa (HS) is strongly associated with Crohn's Disease (CD). HS and CD share clinical similarities and similar inflammatory pathways are upregulated in both conditions. Increased prevalence of inflammatory disease in industrialised nations has been linked to the Western diet. However, gut microbiota composition and diet interaction have not been compared in HS and CD. Here we compared the fecal microbiota and habitual diet of previously reported subjects with HS (n=55), patients with CD (n=102) and controls (n=95). Patients with HS consumed a Western diet similar to that of patients with CD. However, habitual diet in HS and CD was significantly different to controls. Previously, we detected differences in microbiota composition among patients with HS from that of controls. We now show that 40% of patients with HS had a microbiota configuration similar to that of CD, characterised by the enrichment of pathogenic genera (Enterococcus, Veillonella and Escherichia_Shigella) and the depletion of putatively beneficial genera (Faecalibacterium). The remaining 60% of patients with HS harboured a normal microbiota similar to that of controls. Antibiotics, which are commonly used to treat HS, were identified as a covarying with differences in microbiota composition. Measuring the levels of several inflammatory markers highlighted the fact that growth-arrest specific 6 (Gas6), which has anti-inflammatory potential, were significantly lower in the 40% of patients with HS who had a CD microbiota configuration. Levels of the pro-inflammatory cytokine IL-12, which is a modulator of intestinal inflammation in CD, were negatively correlated with the abundance of health-associated genera in patients with HS. In conclusion, the fecal microbiota may help identify patients with HS who are at greater risk for development of CD.